REGIONAL RESEARCHES OF PROFESSOR OF THE LVIV UNIVERSITY Y.P. CIS’ /TO 90-ANIVESARY/ - Кісь, Я. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Regional researches of prominent Ukrainian historian Yaroslav Cis’, who by the scientific labours and teaching activity in the Lviv university in 60th–80th years ХХ age was instrumental in saving of traditions of Ukrainian historiography and domestic study of a particular region, are analysed in the article.